Investigation of the Behaviour of Boundary Elements in Mild Steel Shear Walls with an Externally Bonded Plate to One Boundary Element - Amir Azarpour (The International Journal of Multiphysics, 2025)
Recently, steel shear walls have been utilized as lateral load-resisting systems due to their good seismic performance in the structure as retrofitting and constructions of present ones. Steel shear walls are usually set up in three different ways: with stiffener, without stiffener, and composite, which the second type is more common. A stiffened steel shear wall contains a steel plate surrounded by columns and beams in which the filling plate is completely connected to the boundary elements. In this study, several specimens with different lengths whose inner plates were fully connected to the boundary elements were analyzed in ABAQUS. Then, the steel shear wall’s behaviour with partial length connection was assessed by connecting the plate to one of the boundary members. The outcomes endorse that initial stiffness and the base shear of steel shear walls with partial-length connections are less than those of steel shear walls with full connections. Furthermore, the plate yield stated board in steel shear walls with partial length connection was lower than the amount observed in steel shear walls with full connections. In addition, higher axial forces were applied to the columns in the cases of full connections compared to the other specimens. In the CF cases, the axially compressive force applied to the columns was less than that in the BF mode. In addition, the less bending moment is applied to the BF specimens. It is also concluded that the ductility factor of models with full connection is higher than that of partial-length connection specimens.